Beauty Lies in the Eye of the Beholder - Calder, Judith (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2000)
Best practice can be defined as that combination of structure, educational technology and content of a learning opportunity, which, in certain contexts and for particular groups of learners, is most likely to achieve the purposes of the main stakeholders. However, the rate of change of technological, political, economic, social and cultural contexts suggests that best practice may become a redundant concept, in that what is judged as best one day may not be so judged the next. This article considers what some significant contributions to the literature on open and distance learning practice have to say about the development and provision of best practice and about the place of critical reflection by stakeholders. It also considers the challenges facing the development of best practice presented by change, concluding with the identification of the most significant areas of development yet to be made.